宽厚板轧机主传动接轴的国产化改进 - 周晓峰; 江宇辉 (Jixie Chuandong, 2010)
The design of main drive spindle for the 2nd heavy plate mill line at Xiangtan Iron & Steel Co.,Ltd.is mainly introduced.Based on the domestic material and technology,through the structure improvements of the main drive spindle and reasonable redistribute the safety coefficient of each key part,the safety of the main shaft is ensured.This will be the domestication of heavy plate mill main spindle good examples.